The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12903-021-01671-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of photon-initiated photoacoustic streaming in root canal models with different diameters or tapers

Abstract: Background This study aimed to compare the use of photon-initiated photoacoustic streaming (PIPS) and conventional needle irrigation (CNI) in conjunction with different concentrations of sodium hypochlorite (NaOCl) to remove Enterococcus faecalis (E. faecalis) suspended bacteria and biofilms from root canal systems with different diameters or tapers. Methods Artificial root canal samples (n = 480) were randomly divided into three groups (n = 160/gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…[27,28] Our previous study showed ATP level could re ect the amount of bacteria. [11,29,30] And studies also have found that detection techniques based on ATP bioluminescence correlate well with conventional plate counting methods in food testing. [31] The present study showed that the ATP value of the PIPS group was signi cantly lower than that of the CNI group (P = 0.046), indicating that PIPS irrigation had a better bactericidal effect, which coincided with our previous in vitro research.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…[27,28] Our previous study showed ATP level could re ect the amount of bacteria. [11,29,30] And studies also have found that detection techniques based on ATP bioluminescence correlate well with conventional plate counting methods in food testing. [31] The present study showed that the ATP value of the PIPS group was signi cantly lower than that of the CNI group (P = 0.046), indicating that PIPS irrigation had a better bactericidal effect, which coincided with our previous in vitro research.…”
Section: Discussionmentioning
confidence: 88%
“…[31] The present study showed that the ATP value of the PIPS group was signi cantly lower than that of the CNI group (P = 0.046), indicating that PIPS irrigation had a better bactericidal effect, which coincided with our previous in vitro research. [11] Another randomized clinical trial likewise reported that irrigation with the PIPS device was signi cantly effective in reducing bacterial counts. [12] What's more, other in vitro study found that the use of a combination of NaOCl with PIPS was effective in eradicating E. faecalis and inhibiting new bacterial growth, thus minimizing the possibility of reinfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the ethics board of the School and Hospital of Stomatology, Guangzhou Medical University. A previous study [ 12 ] was used to identify an effect size of 0.50 required to calculate the total sample size for this study. α-type error = 0.05 and power (1 − β) = 0.80 were also inputted (F test family, ANOVA, G*Power for Windows).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, well‐designed laboratory studies using exactly standardized situations allow reproducible comparisons of special devices and settings. Available studies investigating the removal efficacy of biofilm‐mimicking hydrogel used prefabricated tooth models with relatively simple root canal anatomy (Nagahashi et al., 2022; Wen et al., 2021) or straight root canals (De Meyer et al., 2017; Macedo et al., 2014). Only very few studies used severely curved root canals (Peeters et al., 2015; Swimberghe et al., 2021), and only two studies addressed different insertion depths and different tips for laser activated irrigation using the AdVerL EVO (Hoshihara et al., 2021; Kouno et al., 2020).…”
Section: Introductionmentioning
confidence: 99%